Control of bleeding from intercostal artery laceration. (2022) - Sabath, Bruce F.; Lin, Julie; Salahuddin, Moiz; Grosu, Horiana
Abstract: Laceration of an intercostal artery is a rare but potentially catastrophic complication of pleural procedures such as thoracentesis. Recognition of this problem often occurs late in the bleeding process, only after hemodynamic decompensation has occurred. Aggressive and emergent measures are usually undertaken such as angiographic embolization or thoracotomy. In our review of the literature, manual pressure over the pleural space is not described as an intervention in case reports or case series. We demonstrate the first video proof of the immediate success of direct pressure over an intercostal site as a simple, rapid, and effective method for definitively stopping intercostal arterial hemorrhage after a pleural procedure.